Penerapan Metode MOORA dalam Menentukan Juara pada Festival Seni Nasyid - Fira Aulia Nadia; Mesran Mesran (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Nasyid Art Festival is an opportunity for young people, especially Muslim youth who are interested in the field of Islamic music. Usually, in this nasyid art, we often encounter an Islamic organization or every mosque or musholla administrator, there must be an organization called Youth Mosque or BKM (Mosque Management Agency) which will certainly facilitate the development of this cultural art so that it does not become extinct. However, we often find that in a Nasyid Art Festival fraud and KKN (Corruption, Collusion, and Nepotism) often occur in the selection of champions at this nasyid art festival. Therefore the researcher is interested in implementing the MOORA method in solving a problem, after applying the MOORA method in determining the winner in the nasyid festival competition, the final results show that the best alternative with the highest Yi value is the A3 group Salahuddin alternative with a Yi value of 0.4765. The second position is occupied by alternative A2 group Rabbani with a Yi value of 0.4473, while the third position is occupied by alternative A4 group Qhairun with a Yi value of 0.4472